THE FRAMING OF BRIGADIER J’S MURDER IN ONLINE NEWS MEDIA - Salim, Irfan Hanify (Annual International Conferences on Language, Literature, and Media, 2023)
This study embarks on an extensive exploration of recent media coverage concerning the tragic murder of Brigadier J, employing a meticulous combination of framing analysis and corpus linguistics facilitated by specialized linguistic analysis software known as AntConc. The central objective of this research is to conduct a thorough examination of how the Indonesian National Police’s response to Brigadier J’s murder has been portrayed and evaluated in the media. To achieve this, the study adopts a descriptive qualitative approach complemented by the analytical capabilities of AntConc. Through a rigorous analysis of word frequency patterns and linguistic choices in news articles from Tempo and Tribratanews, this study aims to unearth subtle nuances in how these media outlets have depicted the events. The findings reveal strikingly divergent assessments. Tribratanews resolutely throws its support behind the police force, emphasizing its unwavering commitment to upholding the rule of law and rallying public support. In stark contrast, Tempo critically evaluates the professionalism of the police, spotlighting the mishandling of evidence as emblematic of broader issues related to unprofessional conduct within the force. Tempo strategically deploys negation markers to convey its discerning judgment on the matter. Overall, this study sheds light on the multifaceted strategies employed by media outlets when portraying and evaluating intricate news stories, such as the Indonesian National Police’s response to Brigadier J’s murder. These findings not only make a significant contribution to the field of media studies but also provide valuable insights into the complexities and ramifications of media representation.